Current Mobile Applications for The Prevention of Child Sexual Abuse: A Scoping Review - Tetti Solehati; Yanti Hermayanti; Mira Trisyani; Rachelya Nurfirdausi Islamah; Cecep Eli Kosasih (The Indonesian Institute of Science and Technology Research, 2026)
The use of mobile applications in child protection has increased in recent years, including their potential role in preventing child sexual abuse (CSA). However, the extent and nature of evidence supporting mobile application–based interventions for CSA prevention remain unclear. This scoping review aimed to identify, synthesize, and map existing evidence on the development and use of mobile applications for the prevention of child sexual abuse. Following the Arksey and O’Malley framework, a scoping review was conducted using systematic searches in ScienceDirect, CINAHL (EBSCO), and Scopus. Search terms included variations of mobile applications (including mobile and smartphone apps), prevention, and child sexual abuse. Eligible studies were quantitative intervention or mixed-methods studies that evaluated mobile application–based interventions targeting CSA prevention, were available in full text, published in English, and released between 2017 and 2024. Data were extracted manually and synthesized descriptively using thematic analysis. From 3,896 records, four studies met the inclusion criteria. Thematic analysis identified four key themes: (1) improved children’s awareness and protective skills; (2) promotion of self-protective behaviours; (3) enhanced parental knowledge; and (4) usability and accessibility of mobile applications. The available evidence on mobile applications for CSA prevention remains limited and heterogeneous. While existing studies suggest that mobile applications may support awareness-building and short-term preventive outcomes, the current evidence is insufficient to establish effectiveness. Further theory-informed and methodologically rigorous research is needed to evaluate sustained behavioural change, long-term outcomes, and equitable implementation across diverse contexts.